2019
DOI: 10.2147/amep.s210286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors associated with medical students’ choice of psychiatry as future specialty: a cross-sectional study</p>

Abstract: BackgroundDespite the fact that mental illnesses are highly prevalent, shortage of trained human resource, particularly psychiatrists, in the field is disproportionately low. This is especially challenging in developing countries. We report factors affecting medical students’ choice of psychiatry specialty as a future career.MethodsA facility-based cross-sectional study design incorporating demographics, psychiatry specialty choice and a list of factors related to psychiatry was administered to fourth year med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…They also shared the time point at which they decided on their specialty and why they made the decision at that time. The authors compiled these narratives from the focus groups and used content derived from previously validated and published surveys on specialty interests and choice [ 6 11 , 23 , 24 ] to create a 22-question survey. The survey was designed using the Qualtrics Survey Software (Qualtrics, Seattle, WA), which also collected and compiled the responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also shared the time point at which they decided on their specialty and why they made the decision at that time. The authors compiled these narratives from the focus groups and used content derived from previously validated and published surveys on specialty interests and choice [ 6 11 , 23 , 24 ] to create a 22-question survey. The survey was designed using the Qualtrics Survey Software (Qualtrics, Seattle, WA), which also collected and compiled the responses.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that several factors impact specialty decisions including academic interests, lifestyle and work schedule, income, prestige, job market, student debt, board scores, and personality [ 1 5 ]. Students place varying levels of importance on these factors depending on their specialty choice as demonstrated by studies in fields including surgery, emergency medicine, psychiatry, and pathology [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gender is one of these factors, and there has been a beneficial association between the female gender and a positive attitude toward psychiatry (McParland et al, 2003). Prior knowledge of mental illness before entry to medical school, either personally or through having a family member or a friend become mentally ill, was associated with a positive attitude toward psychiatry and a choice in the specialty as a career in another study conducted by Kerebih et al (2019) among medical undergraduates in Ethiopia. This is supported by a survey conducted by Rajagopal et al (2004), which suggests that it could be due to the student's experience knowing or caring for a mentally ill person, which makes the student more comfortable with psychiatry and psychiatric patients.…”
Section: Factors Hindering Medical Students' Interest In Psychiatry I...mentioning
confidence: 99%
“…The people in charge of education play a fundamental role in facilitating and supervising direct contact with patients, promoting coexistence, participating in their treatment, and fostering comprehensive learning (Kerebih, Salelew, & Hailesilassie, 2019;Lyons & Janca, 2015). Various guidelines have been established to achieve objectives within the medical student's training (Sartorius et al, 2010).…”
Section: Introductionmentioning
confidence: 99%